Petroplacus gen. nov. (Bacillariophyta): a new genus of diatom from Lake Baikal - Pomazkina, Galina; Rodionova, Yelena; Sherbakova, Tatyana; Williams, David.m. (Phytotaxa, 2016)
The valve morphology of two raphid diatom taxa from the littoral zone of Lake Baikal has been studied by means of light and electron microscopy. Their characters show obvious affinities to the genera Placoneis and Petroneis. Due to distinctive characters of the internal and external valve structure, however, the two taxa cannot be placed in either of these two genera or any other existing genus. Thus we have described the new genus Petroplacus to accommodate them. Its distinctive characters are: linear-elliptic or broadly-linear valves with protracted rostrate apices, fine radial striation including semi-regular short intercalary striae, the external straight central fissures deep in the T-shaped grooves, direct internal raphe endings and small round poroids internally covered by simple volae. Two species are included: Petroplacus lizae, the generitype, and P. tectum. To date, these species have been found only on the sandy substrate of the western shore of Lake Baikal.